An unusual cause of bilateral diaphragmatic paralysis. Issue 3 (March 1992) - Pandit, A; Kalra, S; Woodcock, A
Abstract : In a patient who had a sudden onset of bilateral diaphragmatic paralysis after forceful neck manipulation complete, though gradual, recovery in lung function and transdiaphragmatic pressures was seen over three years. This is a previously unrecognised risk of neck osteopathy.